Antibacterial Activity of Sea Cucumber Extract and Elucidation of Membrane Synthesis Genes in Staphylococcus Aureus - Mohamed Alipiah, Norfarrah (2011)
Sea cucumber is widely used in South East Asian country folk medicine for the treatment of wound and skin infections. It is a new alternative source of antibiotics that are from valuable biological resource for future commercial development in pharmaceutical use. This study investigated the antibacterial activity of Stichopus badionotus methanolic extract to elucidate its use in traditional medicine. Antimicrobial activity was assayed by the disc diffusion and broth macro dilution method. From the results, it appeared that the methanolic extract of S. badionotus displayed antibacterial activities against three non resistant and three multiple resistant strains of Staphylococcus aureus. The 3.75 mg/mL minimum inhibitory concentration (MIC) value of the extract successfully inhibited the growth of non resistant S. aureus (MSSA) and against multi resistant strains of S. aureus (MRSA) the effective MIC value is 7.50 mg/mL. The S. badionotus extract then combined with the antibiotics, penicillin and ampicillin gave fractional inhibitory concentration (FIC) as low as 0.375 indicating synergism activity of the mixture against MSSA and MRSA strains. This activity indicates the lower concentration usage of antibacterial agents in inhibiting resistant strains of S. aureus. Furthermore, based on healing rates and dosage tests in rats with wound infection model, the combination treatment of extract and antibiotics was better than antibiotic alone treatment. With the low dosage in-combination treatment of the S. badionotus extract 0.94 mg/mL combine with penicillin 0.125 mg/mL or ampicillin 0.05 mg/mL, the wound healed by day 6. While single treatment using high dosage of antibiotic ampicillin 0.2 mg/mL heals on day 5. These results indicate the potential of S. badionotus extract to become alternative choices of antimicrobial agents for in combination mode of treatment against MRSA infection. MRSA strains treated with S. badinotus extract exhibited inhibitory activity as shown by the plate and tube assays. The extract then proofs to interrupt selected genes encoding for cytoplasmic membrane of bacterial structures that are important for bacterial survival. Disruption in membrane integrity will result in leakage of internal contents followed by cell death suggest the membrane a practical drug target. Based on the bacterial needs to have membrane, studies on MRSA membrane synthesis genes, msrR and mprF, were conducted via reverse transcriptase polymerase chain reaction approach. Alteration of nucleotide sequences at the RNA level after treatment was observed only in the mprF gene but not in the msrR gene. The nucleotide changes were up to 35% for MSSA isolates and < 10% for MRSA isolates, which both contribute to < 50% changes in protein base after translation. A confirmatory experiment, fluorescence assay, used in confirming this gene as a drug target predicted by molecular assays revealed positive results. The extract specifically acts on the MRSA membrane, shown through this assay by the uptake of fluorescent dye upon rupturing of the bacterial membrane after treatment with the extract. The S. badionotus extract treatment on MRSA at the MIC level disrupts the membrane after 60 min upon application, showed by a steep curve of the fluorescence intensities indicating the membrane leakage. Selective targeting of the mprF gene by the S. badionotus extract is an invaluable finding requiring further investigation into the feasibility of utilizing this target gene in the development of anti-infective agents against MRSA.